Ultrasensitive room-temperature acetone gas sensors employing green-solvent-processed aligned InNdO nanofiber field-effect transistors. Issue 3 (5th January 2022) - Li, Jun; Li, Linkang; Chen, Qi; Zhu, Wenqing; Zhang, Jianhua
Abstract : Aligned InNdO nanofiber FETs prepared with green solvents by an electrospinning method for acetone gas detection at room temperature. Abstract : The development of a high-performance acetone gas sensor for detecting low concentrations of acetone gas is still a key issue. Here, we propose a green-solution-processed electrospinning technique to construct Nd-doped aligned In2 O3 nanofiber field-effect transistors. Benefitting from electron transport, the aligned InNdO nanofiber field-effect transistor (FET) exhibits a high mobility of 5.5 cm 2 V −1 s −1 and an on/off current ratio of 10 7 . As a result, when used in acetone gas sensors, the gas sensor showed excellent properties for acetone detection at room temperature (20 °C), including high response (88) under 4 ppm, a fast response and recovery time (31/53 s), a relatively low detection limit (69 ppb) and acceptable selectivity of acetone gas. In addition, capacitance–voltage ( C – V ) analysis was used to further explore the internal mechanism of acetone sensing. This work offers an efficient and novel strategy to design high-performance acetone gas sensors for ppb-level detection at room temperature (20 °C).